Qing`e Pill Inhibits Osteoblast Ferroptosis via ATM Serine/Threonine Kinase (ATM) and the PI3K/AKT Pathway in Primary Osteoporosis - Jian Hao; Jiaxin Bei; Zhenhan Li; Mingyuan Han; Boyuan Ma; Pengyi Ma; Xianhu Zhou (Frontiers in Pharmacology, 2022)
Osteoporosis (OP) is an aging-related disease that is the main etiology of fragility fracture. Qing’e Pill (QEP) is a mixture of traditional Chinese medicine (TCM) consisting of Eucommia ulmoides Oliv., Psoralea corylifolia L., Juglans regia L., and Allium sativum L. QEP has an anti-osteoporosis function, but the underlying mechanism remains unclear. In this study, online databases were employed to determine the chemical compounds of QEP and potential target genes in osteoporosis. Potential pathways associated with genes were defined by Gene Ontology (GO) and Kyoto Encyclopaedia of Genes and Genomes (KEGG) databases. A compound–target–disease network was constructed. Hub genes screened through Cytoscape were intersected with the FerrDB database. The potential key genes were validated in HFOB 1.19 cells, and rat models were ovariectomized through Western blot, RT-qPCR, ELISA, HE staining, immunohistochemistry, and immunofluorescence analyses. The intersection targets of QEP and osteoporosis contained 121 proteins, whereas the target–pathway network included 156 pathways. We filtered five genes that stood out in the network analysis for experimental verification. The experiments validated that QEP exerted therapeutic effects on osteoporosis by inhibiting ferroptosis and promoting cell survival via the PI3K/AKT pathway and ATM. In conclusion, combining the application of network analysis and experimental verification may provide an efficient method to validate the molecular mechanism of QEP on osteoporosis.